PERBAIKAN GEOMETRIK TRASE JARINGAN JALAN DENGAN MENGGUNAKAN TEKNOLOGI PENGINDERAAN JAUH DAN SISTEM INFORMASI GEOGRAFIS - Sukojo, Bangun Muljo; Kustarto, Hendro (Makara Journal of Science, 2002)
Geometric Improvement Of Trace Network Road with Remote Sensing and Geographic Information System. Together with a great development in road network at such district, it must be followed by changing information that should be suited to the condition at present. For supporting the information changes, the remote sensing technology could be applied. It is one of technology with a great increment and needed to various applications. The application of remote sensing technology is close related to spatial field which is used to be achieved from non digital because of limitation facilities and other obstacle. However with remote sensing technology, those can not be burdened anymore and the information achieved can be updated. The presence of remote sensing technology is followed by emerging of Geographic Information System technology which promises a new era in providing deep information and spatial object analysis. The object identification through Landsat Thematic Mapper (LTM) image with (30x30) meter spatial and 7 (seven) band spectral resolution. The composite image together with image contrast improvement are applied to supervised classification covered object for obtaining classified and corrected image that can be used to analyze network road improvement and create database information of trace network road using Geographic Information system.